Studi Komparasi Kebijkan Pemerintah Indonesia dengan Umar Bin Khattab dalam Penetapan Harga - Laily, Nuri Ma'rifatul (Jurnal Ilmiah Ekonomi Islam, 2023)
The soaring price of cooking oil made the government issue a policy of fixing one price for cooking oil. However, the impact of this policy was a shortage of oil in Indonesia. The purpose of this study is to find out the similarities and differences between government policies and Umar bin Khattab's policies in price fixing and to find out the factors of government failure in implementing cooking oil HTE policies. This type of research is a descriptive qualitative research library. The results of this study indicate that there are many similarities in government policies with Umar bin Khattab in setting prices. However, there are differences in terms of the target object that will benefit, the government is more inclined towards the benefit of consumers without providing feedback to producers. The cause of the government's failure to implement the HET for cooking oil is the difference between the buying and selling system of traditional markets and modern markets, the existence of panic buying from the public, and the hoarding of cooking oil by several parties.